India's informal trade with Pakistan - Nisha Taneja; Samridhi Bimal (Indian Council for Research on International Economic Relations (ICRIER), 2016)
Informal trade continues to thrive between India and Pakistan despite recent measures undertaken by the two countries to normalize trade and reduce transport impediments. This calls for an in-depth analysis of India's informal trade with Pakistan. This study (i) identifies factors determining informal trade, (ii) prepares estimates of India's informal trade with Pakistan (iii) examines the modalities of informal trade (iv) analyzes the transaction cost incurred in trading formally and informally and (v) proposes recommendations needed to shift informal trade to formal channels. The analysis, carried out on the basis of an extensive survey conducted in India and Dubai estimates informal trade to be US 4.71 billion. Of this, India's exports to Pakistan are estimated to be USD 3.99 billion and imports from Pakistan USD 0.72 billion. The study concludes that informal traders in India and Pakistan have developed efficient mechanisms for contract enforcement, information flows, risk sharing and risk mitigation. Further, even though the transaction costs of trading in the informal channel are significantly higher than the formal channel, traders prefer to trade through the informal channel since it is more efficient than the formal channel. An important policy implication is that unless the environment of the formal trade improves, informal trade will not only continue to coexist with formal trade, but it will also impact its potential magnitude in the coming years.
Keywords: F10; F13; F50; 330; India-Pakistan; informal trade; regional integration